The Nature of Truth in Evaluating Arabic Language Learning Through the Epistemological Representation of Language Proficiency - Adibah Ulaya Putri; Sofyan Sauri (Cetta: Jurnal Ilmu Pendidikan, 2026)
Evaluation in Arabic language learning is generally assumed to represent students’ language competence, yet this assumption is rarely examined from an epistemological perspective. In practice, there is often a gap between students’ test scores and their actual communicative ability. This condition indicates that the current evaluation system does not always reflect students’ real language performance. Therefore, this study aims to examine the concept of truth in Arabic language learning evaluation through the perspectives of correspondence theory, coherence theory, and pragmatism. This study employed a qualitative library research method, analyzing primary and secondary sources, including scientific journal articles and academic works on Arabic language evaluation, epistemology, and the philosophy of education. The findings reveal several interconnected problems. From the perspective of correspondence theory, the dominance of grammar-based written tests often yields scores that do not align with students’ actual communicative competence, as evidenced by students who achieve high scores yet still struggle with oral Arabic. From the perspective of coherence theory, there is a mismatch between communicative learning objectives and evaluation instruments that remain focused on grammatical and cognitive aspects. Meanwhile, from a pragmatic perspective, the strong emphasis on grades and passing examinations has shifted evaluation from a reflective learning tool into an end in itself, reducing its contribution to the development of meaningful language skills. This study concludes that improving Arabic language evaluation requires not only technical changes but also a philosophical reorientation toward more authentic and meaningful assessment practices.